Tribotehnichnical wear capability of gasometrical covering - Щепотьєв, О.І.; Варюхно, В.В.; Кузьменко, Т.І.; Бурдюженко, Л.В. (Proceedings of National Aviation University (archive), 2004)
The experimental studies of the element –organic influence additive will presented on regularities of covering, are installed main trybotechnical processes, which is a result the resistance covering.